2008
DOI: 10.1021/ef8002944
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphoric Acid (PPA)-Modified Bitumen: Disruption of the Asphaltenes Network Based on the Reaction of Nonbasic Nitrogen with PPA

Abstract: Relatively little is known about the effect of polyphosphoric acid (PPA) on bitumen chemistry and structure. In an effort to increase this understanding, the reaction of indole with PPA was studied by Fourier-transform infrared spectroscopy (FTIR). Indole contains a pyrrole functional group very common in bitumen. The results revealed that both the amine and the double bond of indole can be reactive, and that indole concentration affected the reaction pathway. All reactions began with the protonation of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 12 publications
0
26
0
3
Order By: Relevance
“…To date many chemical agents have been introduced for the target of bitumen modification, such as: organo-metallic compounds [113,114], sulfur (S) [66,[115][116][117][118][119][120][121], polyphosphoric acid (PPA) [122][123][124], sulfonic acid [125], carboxylic anhydrides [126][127][128], silanes [129,130], thiourea dioxide [131], nanocomposite-modified bitumen [132][133][134][135][136][137][138][139][140], and reactive polymers [141][142][143][144][145][146][147][148][149][150][151][152][153][154][155]. However, from the above-mentioned chemical compounds only a few of them have been used practically.…”
Section: Bitumen Chemical Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…To date many chemical agents have been introduced for the target of bitumen modification, such as: organo-metallic compounds [113,114], sulfur (S) [66,[115][116][117][118][119][120][121], polyphosphoric acid (PPA) [122][123][124], sulfonic acid [125], carboxylic anhydrides [126][127][128], silanes [129,130], thiourea dioxide [131], nanocomposite-modified bitumen [132][133][134][135][136][137][138][139][140], and reactive polymers [141][142][143][144][145][146][147][148][149][150][151][152][153][154][155]. However, from the above-mentioned chemical compounds only a few of them have been used practically.…”
Section: Bitumen Chemical Modifiersmentioning
confidence: 99%
“…Among the different acids that can be used to improve bitumen properties through chemical modification, polyphosphoric acid (PPA) has been studied in numerous papers and patent publications [172][173][174][175][176][177][178][179][180][181][182][183][184][185]. From a chemical point of view PPA is an oligomer of phosphoric acid (H 3 PO 4 ), with no free water, which may have more than 10 repeating units [122].…”
Section: Ppa-based Techniquesmentioning
confidence: 99%
“…PPA modified asphalt binder and mixture have been successfully applied in construction field [4][5][6]. However, the effect of PPA additives on the pavement engineering performances is profound, and the mechanism of PPA affect bitumen is complex.…”
Section: Introductionmentioning
confidence: 99%
“…9 In efforts to verify this postulate and better establish the nature of the reaction between PPA and bitumen, we resorted to the use of bitumen model compounds. 10,11 In working with nitrogenated compounds, it was found that PPA could act as a simple acid to produce ionic-pairs 10 or facilitate intermolecular coupling, 11 and that it could also be a reactive catalyst that produces phosphorylated amines. 11 Here, we report on the reaction of PPA with four oxygenated bitumen model compounds, heated alone or together with PPA ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In working with nitrogenated compounds, it was found that PPA could act as a simple acid to produce ionic-pairs 10 or facilitate intermolecular coupling, 11 and that it could also be a reactive catalyst that produces phosphorylated amines. 11 Here, we report on the reaction of PPA with four oxygenated bitumen model compounds, heated alone or together with PPA ( Figure 1). They are representatives of compounds with phenol, ether, ketone, and carboxylic acid functionalities.…”
Section: Introductionmentioning
confidence: 99%